EFFECTS OF POINT-PIN REWARD METHOD TOWARDS STUDENTS’ INTEREST AND ACQUISITION - Nanik - Setyaningsih; Djukri Djukri (Universitas Negeri Yogyakarta, 2020)
This study was aimed at determining the effect of the point-pin reward method in Biology cross-specialization learning activities towards students’ interest and acquisition in the 11th-grade social science class in State Senior High School 1 Sentolo. The research was a quasi-experimental study using a pre-test and post test non-equivalent control group design. The number of participants consisted of 41 students divided into 2 classes, the control class and the experimental class. Data for students’ interest in learning were collected using interest questionnaires analyzed using a Likert scale. Data for students’ acquisition were obtained by analyzing written tests. Research data were analyzed using independent-samples t test. The results of this study indicate that: The point-pin reward method has significant effects on the students’ interest and acquisition in the learning activities of biology cross-specialization lessons.